SIMULATION STUDY ON FUEL COMBUSTION OF WATER-TUBE BOILER IN PALM OIL MILL - AHMAD BADARUDDIN, NUR AQILAH (IRC, 2021)
Water-tube boilers are useful for steam turbine power generation and the best method to convert chemical energy in fuel through combustion into mechanical energy which runs the steam turbine to generate electricity.